Gastroenterological Surgery and Management of Clostridioides difficile Infection: A Review - Tomonori Takano; Hiroyuki Aiba; Mitsuo Kaku; Hiroyuki Kunishima (Journal of the Anus, Rectum and Colon)
Fever and diarrhea are the common symptoms of Clostridioides difficile infection (CDI); however, pseudomembranous enteritis, megacolonization, and paralytic ileus have been observed in severe cases. C. difficile spores are resistant to several types of disinfectants. Thus, they are often the causative pathogens of healthcare-associated infections. Rapid diagnostic tests based on glutamate dehydrogenase and toxins are the mainstay of CDI laboratory diagnosis owing to their simplicity. CDI can be diagnosed with high specificity using the nucleic acid amplification test, a genetic test for C. difficile toxins. The risk factors for CDI include age 65 years; history of antimicrobial use; previous hospitalization; history of gastrointestinal surgery, chronic kidney disease, or inflammatory bowel disease; nasal tube feeding; and use of proton pump inhibitors and histamine H2 receptor antagonists. The risk of CDI development persists even 1 year after discontinuation of proton pump inhibitor use. Furthermore, colorectal surgery and radical cystectomy with urinary diversion are associated with high incidences of postoperative CDI. The choice of therapeutic agent depends on the severity of the disease and recurrence. However, a combination of oral or nasogastric vancomycin, intracolonic vancomycin, and intravenous metronidazole can be considered in patients with toxic megacolonization and paralytic ileus. In January 2024, the European Committee on Antimicrobial Susceptibility Testing established a breakpoint for fidaxomicin (minimum inhibitory concentration breakpoint > 2 mg/L) against C. difficile. Rapid progress has been achieved in CDI treatment. Thus, multidisciplinary teams must collaborate to diagnose, treat, and control CDI.